2013
DOI: 10.17221/217/2012-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Integration and characterization of T-DNA insertion in upland cotton

Abstract: : Integration and characterization of T-DNA insertion in upland cotton. Czech J. Genet. Plant Breed., 49: 51-57.Copy numbers were evaluated by real-time quantitative PCR, and 149 junctions of T-DNA were isolated by thermal asymmetric interlaced PCR from 92 independent transgenic cotton lines transformed by Agrobacterium tumefaciens strain LBA4404. Real-time quantitative PCR results showed that 46% had integration of one or two T-DNA copies, 54% had three or more copies. Among 63 amplified products at LB juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The integration of transgenes near or within a microsatellite sequence could result in the absence or presence of one or more ISSR markers (DNA bands), altering the DNA profiles of the untransformed sample. This can be assumed since there are reports of transgene integration between microsatellite-like sequences (Yang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The integration of transgenes near or within a microsatellite sequence could result in the absence or presence of one or more ISSR markers (DNA bands), altering the DNA profiles of the untransformed sample. This can be assumed since there are reports of transgene integration between microsatellite-like sequences (Yang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Zeng, et al (2008) Detected a percentage of 76.7% in transgenic birch plants contained some DNA of the vector backbone. Yang, et al, (2013) reported a percentage of co-transformation of the vector backbone with 51% among 63 amplified products at left border junctions, 30% preserved a fraction of Left border varied from three to 23 base pairs.…”
Section: Southern Hybridizationmentioning
confidence: 99%
“…Như vậy, gen AGPopt đã được chuyển thành công vào các dòng thuốc lá K326. Một số nghiên cứu cho thấy không chỉ số lượng bản copy gây ảnh hưởng đến sự biểu hiện của gen mà vị trí chèn của gen chuyển trong genome cũng đóng vai trò rất quan trọng (Yang et al, 2013). Vì vậy, cần có những nghiên cứu tiếp theo để đánh giá khả năng biểu hiện gen ở các dòng cây.…”
Section: Bpunclassified